Water evaporation particularities in the process of forest fire extinguishing - Strizhak P. A. Pavel Alexandrovich; Volkov R. S. Roman Sergeevich; Vysokomornaya O. V. Olga Valeryevna; Voytkov I. S. (2015, 2015)
Title screen